STRATEGIC LEADERSHIP AND MOTIVATION INFLUENCING THE PERFORMANCE EFFICIENCY OF POLICE OFFICERS UNDER THE PROVINCIAL POLICE REGION 7 - Noichan, Wanchak; Suvannasriha, Christina (Journal of MCU Nakhondhat, 2025)
This research article aimed to 1) Examine the levels of strategic leadership, work motivation, and work performance among police officers under Provincial Police Region 7. 2) Investigate the factors related to work performance, including the relationships between strategic leadership, motivation, and work performance and 3) Analyze how strategic leadership and work motivation influence the work performance of police officers under Provincial Police Region 7. A quantitative research design was employed. The population consisted of 10,495 police officers, and a sample of 400 officers was determined using Taro Yamane’s formula with probability sampling. The research instrument was a questionnaire validated for content validity using the Index of Item–Objective Congruence (IOC) and tested for reliability using Cronbach’s alpha coefficient which showed high internal consistency. Data were analyzed using descriptive statistics Pearson’s correlation coefficient, and multiple regression analysis. The results revealed that 1) Police officers demonstrated the highest level of strategic leadership (mean = 4.27) the highest level of work motivation (mean = 4.38) and the highest level of work performance (mean = 4.30) 2) Work performance was highly and positively correlated with work motivation (r = 0.899) and strongly correlated with strategic leadership (r = 0.820) with both relationships statistically significant at the .01 level and 3) Regression analysis indicated that work motivation had the greatest influence on work performance ( = 0.663) followed by strategic leadership ( = 0.303).